The Impact of Electronic Payment Technologies on the Quality of Accounting Information: An Applied Study on Electronic Payment - Hussein, Mustafa M.; Hasan, Mustafa S.; Mohamad, Waleed N. (PROSPECTIVE RESEARCHES, 2026)
This research aims to demonstrate the impact of electronic payment technologies on the quality of accounting information at electronic payment outlets operating in Salah al-Din Governorate. Electronic payment technologies were represented by three main axes: mobile payments, e-wallets, and electronic payment cards, which served as the independent variable. The quality of accounting information was represented by the two characteristics of relevance and faithful representation, which served as the dependent variable. The research adopted a descriptive-analytical approach and relied on a questionnaire distributed to (30) electronic payment companies. The data were analyzed using the SPSS statistical software with a five-point Likert scale. The results showed that electronic payment technologies have a significant and positive impact on the quality of accounting information. E-wallets were found to be the most influential technology in increasing the accuracy and reliability of accounting data, followed by electronic payment cards and then mobile payments. The results also indicated that adopting these technologies contributes to improving the characteristics of relevance and faithful representation through faster transaction processing, reduced human error, and enhanced traceability and transparency. Based on the findings, the research recommends developing accounting systems at electronic payment outlets to automatically integrate them with modern payment technologies. This will ensure the immediate updating of financial data and enhance the reliability and accuracy of reports. It also calls for training staff in accounting and technology to keep pace with digital transformation and achieve integration between electronic payment systems and traditional accounting systems.